Assessment of sodium fluoride 2% as a new method of disinfecting extracted human teeth - CARVALHO,Monize Ferreira Figueiredo de (2016)
ABSTRACT Objective: Investigate the action of sodium fluoride 2% as a new method of disinfecting/sterilizing extracted human teeth, using E. faecalis. Methods: The survival rate of E. faecalis ATCC 29212 was assessed, in terms of absorbance from the culture media, using a spectrophotometer. The sterilization assessment was carried out in the following groups: Group I (GI) - control; GII - autoclave; GIII - sodium fluoride seven days; GIV - sodium fluoride 14 days. Results: When using the autoclave and sodium fluoride solution (2%), the quantity of bacteria reduced significantly when compared to the control group (p <0.001). Statistically significant differences were also found when the experimental groups were compared with each other (p < 0.001). Conclusion: The results of the present study suggest that sodium fluoride 2% solution can be considered a new disinfection method based on its capacity to reduce the load of E. faecalis.